"We've toiled without end": Publicity, Crisis, and the Suicide "Epidemic" in Greece. (5th October 2015) - Davis, Elizabeth
Abstract This paper addresses the rising suicide rate in Greece since the economic crisis began in 2008. By 2011, Greek and international media were reporting the Greek suicide rate as the fastest rising in Europe; dozens of "spectacular" public suicides were taken as symptoms of an "epidemic." In this paper, I explore different accounts of this "epidemic": statistical studies and press reports on suicide since the crisis; notes written by people who committed or attempted suicide in public during the crisis; and narratives of suicidality from psychiatric patients before the crisis, in dialogue with local psychiatric epidemiologies. These accounts summon three axes of comparison around suicide in Greece: historical difference, defined by the economic crisis and the time before; locale, contrasting the public sphere of media coverage and consumption with a particular region distinguished by its "suicidogenic" features; and evidence, moving from the public discourse on suicide to clinical ethnographic research that I conducted in northeastern Greece a decade ago. I show that each way of accounting for suicide challenges the epistemologies and evidence at work in the others; the tensions and the interactions among them are signs of indeterminacy in suicide itself, taken as an object of inquiry. In the public discourse on the Greek crisis, the many meanings of suicide have been condensed and fixed as a politics of protest. Yet, I argue, comparison among epistemologies of suicide and recognition of its indeterminacy generate a space for thinking about suicide beyond the publicity of the crisis.